Carbon nanotubes promote alveolar macrophages toward M2 polarization mediated epithelial-mesenchymal transition and fibroblast-to-myofibroblast transdifferentiation. Issue 5 (28th May 2021) - Zhang, Xiang; Luo, Min; Zhang, Jiaxiang; Yao, Zhuomeng; Zhu, Jiaojiao; Yang, Shuxin; Zhu, Qixing; Shen, Tong
Abstract: With substantial progress of nanotechnology, carbon nanotubes (CNTs) are widely used in a variety of industrial and commercial applications. There is rising concern about potential adverse health effects, such as pulmonary fibrosis, related to inhalation of CNTs. The detailed cellular and molecular mechanisms of pulmonary fibrosis induced by CNTs are still not clear. Epithelial-mesenchymal transition (EMT) and fibroblast-to-myofibroblast transdifferentiation (FMT) are considered as critical events in pathogenesis of pulmonary fibrosis. Alveolar macrophages (AMs) polarization plays a key role of regulating EMT and FMT in pulmonary fibrosis. In this study, we applied CNTs to stimulate primary mouse AMs under M1 or M2 polarization conditions, then analyzed the proportion of F4/80 + CD11c + or F4/80 + CD206 + AMs, mRNA expression and activities of iNOS or Arg-1, as well as mRNA expression and content of TNF-α and IL-6 or TGF-β and IL-10 to evaluate dynamic phenotypic and functional changes of AMs. Single-walled CNT (SWCNT), short-type multi-walled CNT (MWCNT), and long-type MWCNT exposure at dose of 50 µg/ml promote AMs polarization toward M1 phenotype at early stage, while promote AMs polarization toward M2 phenotype at late stage. The roles of AMs polarization during development of EMT and FMT were further investigated by conditioned medium (CM) experiments. CNTs-activated M2 AMs promote progression of EMT and FMT via secreting TGF-β. Furthermore, up-regulating IRF4 may be involved in CNTs-induced M2 AMs polarization. In conclusion, this study demonstrates a new insight that CNTs exposure promotes AMs polarization toward M2 phenotype which facilitate EMT and FMT through secreting TGF-β.